Recommendation of the Healthcare System of the Chinese Elderly Group with IoT Technology Based on Responsible Innovation. Issue 2 (2020) - Sun, Yaguang; McDonagh, Deana; Liepert, Susan; Hadinezhad, Shafagh; Oladeji, Faithful
No abstract available